Perception and Usage of Telemedicine Among National Health Insurance Participants in Padang City - Shelvy Haria Roza; Ayulia Fardila Sari (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
The existence of a policy on the use of telemedicine in health facilities is applied almost all over the world. In Indonesia, Padang is one city of the achievements in that the use of telemedicine services remains low, even after the implementation of regulations on telemedicine services. This study aimed to determine the perceived convenience and benefits of using telemedicine services among National Health Insurance participants through the Technology Acceptance Model (TAM). This study was a cross-sectional survey. The sample of this study consisted of 100 National Health Insurance respondents registered at a first-level healthcare facility. The samples were collected using consecutive sampling and online questionnaire sheets carried out for three months in 2021. The analysis includes univariate, bivariate, and multivariate analysis. The results showed that 55% of respondents had a high level of accessibility in getting health services by using telemedicine, 54% of respondents had a good experience related to telemedicine officer services, 94% of respondents had perceptions of illness exist positive, 89% of respondents said that they had a perception of ease in using telemedicine services, and 80% of respondents had a perceived the benefits of telemedicine services. The utilization of telemedicine was affected by accessibility (p=0.000), staff service (p=0.000), perceived ease of use (p=0.022), and perceived benefit (p=0.001). The multivariate analysis indicated that the officer service was the most influencing the use of telemedicine services (OR=3.669). Healthcare facilities should improve their service quality and apply a more accessible and more valuable service for patients as end users.